The Relationship between Central Auditory Processing, Language, and Cognition in Children Being Evaluated for Central Auditory Processing Disorder - Brenneman, Lauren; Cash, Elizabeth; Chermak, Gail D.; Guenette, Linda; Masters, Gay; Musiek, Frank E.; Brown, Mallory; Ceruti, Julianne; Fitzegerald, Krista; Geissler, Kristin; Gonzalez, Jennifer; Weihing, Jeffrey (Journal of the American Academy of Audiology, 2017)
Pediatric central auditory processing disorder (CAPD) is frequently comorbid with other childhood disorders. However, few studies have examined the relationship between commonly used CAPD, language, and cognition tests within the same sample.The present study examined the relationship between diagnostic CAPD tests and “gold standard” measures of language and cognitive ability, the Clinical Evaluation of Language Fundamentals (CELF) and the Wechsler Intelligence Scale for Children (WISC).A retrospective study.Twenty-seven patients referred for CAPD testing who scored average or better on the CELF and low average or better on the WISC were initially included. Seven children who scored below the CELF and/or WISC inclusion criteria were then added to the dataset for a second analysis, yielding a sample size of 34.Participants were administered a CAPD battery that included at least the following three CAPD tests: Frequency Patterns (FP), Dichotic Digits (DD), and Competing Sentences (CS). In addition, they were administered the CELF and WISC. Relationships between scores on CAPD, language (CELF), and cognition (WISC) tests were examined using correlation analysis.DD and FP showed significant correlations with Full Scale Intelligence Quotient, and the DD left ear and the DD interaural difference measures both showed significant correlations with working memory. However, ∼80% or more of the variance in these CAPD tests was unexplained by language and cognition measures. Language and cognition measures were more strongly correlated with each other than were the CAPD tests with any CELF or WISC scale. Additional correlations with the CAPD tests were revealed when patients who scored in the mild–moderate deficit range on the CELF and/or in the borderline low intellectual functioning range on the WISC were included in the analysis.While both the DD and FP tests showed significant correlations with one or more cognition measures, the majority of the variance in these CAPD measures went unexplained by cognition. Unlike DD and FP, the CS test was not correlated with cognition. Additionally, language measures were not significantly correlated with any of the CAPD tests. Our findings emphasize that the outcomes and interpretation of results vary as a function of the subject inclusion criteria that are applied for the CELF and WISC. Including participants with poorer cognition and/or language scores increased the number of significant correlations observed. For this reason, it is important that studies investigating the relationship between CAPD and other domains or disorders report the specific inclusion criteria used for all tests.
Keywords: central auditory processing disorder; dichotic listening; neuroaudiology; temporal processing